A Potential Approach for Converting Rubber Waste into a Low-Cost Polymeric Adsorbent for Removing Methylene Blue from Aqueous Solutions - Mohamed Ibrahim bin Mohamed Tahir; Muhammad Aliyu; Abdul Halim Abdullah (Universitas Gadjah Mada, 2022)
Exploiting waste materials to make cost-effective adsorbents and waste management methods are gaining more attention. In the current study, rubber wastes derived from dipping tank coagulum (DTC) in the glove manufacturing industry were converted into a novel polymeric-adsorbent via a simple sulfonation reaction with concentrated sulphuric acid and was used for the adsorption of methylene blue (MB) dye from aqueous solutions commonly found in contaminated waters. FT-IR, EDX, FESEM, and BET techniques were used to characterize the rubber waste before and after modification. The highest MB removal efficiency of 99.03% was achieved in the condition of initial concentration, adsorbent dosage, pH, contact time, and temperature were 15 mg/L, 30 mg, pH 7, 300 min, and 25 °C, respectively. The adsorption of MB was analyzed using experimental data fitted in a monolayer isotherms model with a maximum adsorption capacity of 119 mg/g. The kinetic model was revealed to agree with the pseudo-second-order kinetic model. Furthermore, SRW retained 90.45% of the removal percentage after four cycles of the repeated adsorption-desorption process. Conclusively, these findings suggest that rubber waste could be a suitable low-cost adsorbent to remove organic dyes from polluted water.